Aberrant methylation of the PTCH1 gene promoter region in aberrant crypt foci. Issue 2 (21st September 2012) - Peng, Liang; Hu, Jingjing; Li, Shujun; Wang, Zhongqiu; Xia, Bingqing; Jiang, Bo; Li, Bingsheng; Zhang, Yu; Wang, Jing; Wang, Xinying
Abstract: Patched homolog 1 (PTCH1) is a known tumor suppressor that regulates the Hedgehog (Hh) pathway and has been implicated in tumorigenesis. The role of PTCH1 in colon carcinogenesis, however, is controversial. The aim of the present study was to investigate epigenetic modifications of PTCH1 in aberrant crypt foci (ACF), the earliest precursor lesion of colorectal cancer (CRC). Using laser‐capture microdissection (LCM), a pure population of ACF epithelial cells was isolated and studied. The inherent protein expression levels of SHH, PTCH1, SMO and GLI1 were assessed by immunohistochemistry for 405 ACF, including 54 dysplastic ACF (d‐ACF) and 351 non‐dysplastic ACF (n‐ACF). The mRNA levels and methylation status of PTCH1 were also determined in 54 d‐ACF and 96 n‐ACF. Our data showed that the expression of SHH, SMO and GLI1 was significantly up‐regulated in d‐ACF, compared to n‐ACF. Also, the mRNA and protein levels of PTCH1 were lower in d‐ACF than n‐ACF. Using MSP or MS‐HRM, PTCH1 methylation was present in 64.8% (35/54) or 63.3% (34/54), respectively, of d‐ACF and 19.8% (19/96) or 22.9% (11/48), respectively, of n‐ACF. PTCH1 methylation was more frequent in d‐ACF than n‐ACF ( p < 0.001) and was associated with PTCH1 mRNA levels ( r = 0.358, p < 0.01). There was a statistically significant correlation between PTCH1 methylation status and the prevalence of colorectal neoplasms. In conclusion, this study suggests that aberrant methylation of the PTCH1 promoter may be an early, initiating event of colon carcinogenesis. Abstract : What's new? The Hedgehog (Hh) signaling pathway plays an important role in many types of cancer. PTCH1 is a tumor‐suppressor gene that induces the activation of the Hh pathway. In this study, the authors investigated epigenetic changes in PTCH1 in colorectal tumors and precancerous cells. They found that altered methylation of PTCH1 correlated with Hh pathway activation in the precancerous cells, and that it was also present in colorectal neoplasms. These findings suggest that aberrant methylation of PTCH1 is an early event in colon carcinogenesis.